Social Library mobile application - Ooi, Xue Ting (2019)
Library is a place with many resources which can be an essential aspect part of our life. Visiting the library allows information seeker of any income level or background to access information they need. People who love reading can also visit the library to access books available to their interest. As such, a library is a place that offers information seeker to discover interesting books.